2018
DOI: 10.18551/rjoas.2018-12.28
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Production, Exports Price, Exchange Rate, Grateks-2/Gernas Policy, and Export Duties on Cocoa Commodity Exports in South Sulawesi, Indonesia

Abstract: The objective of this research is to analyze the influence of production, exports price, exchange rate, Grateks-2/Gernas policy, and export duties policy on cocoa exports in South Sulawesi using data from 1986 until 2015 and employing an analysis technique of Error Correlation Model (ECM). This study has already found that cocoa production, exports price, long-terms and short-terms exchange rate give a positive influence, while the production rate gives a significant influence on cocoa exports in South Sulawes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…Meanwhile (Panti, 2018) found a significant positive exchange rate of 62.5 percent for non-oil and gas exports in East Java with the destination country of America. In contrast to research (Hasbiullah et al, 2018) which found that cocoa production, prices, and export duties were significant for the increase in cocoa exports. While the exchange rate and Grateks-2/Gernas have no significant effect on cocoa exports in South Sulawesi.…”
Section: Effect Of Exchange Rate Inflation Fdi and Domestic Consumpti...contrasting
confidence: 86%
“…Meanwhile (Panti, 2018) found a significant positive exchange rate of 62.5 percent for non-oil and gas exports in East Java with the destination country of America. In contrast to research (Hasbiullah et al, 2018) which found that cocoa production, prices, and export duties were significant for the increase in cocoa exports. While the exchange rate and Grateks-2/Gernas have no significant effect on cocoa exports in South Sulawesi.…”
Section: Effect Of Exchange Rate Inflation Fdi and Domestic Consumpti...contrasting
confidence: 86%